2018
DOI: 10.1017/s0007114518002386
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of food texture introduction in French children aged 4–36 months

Abstract: The aims of this study were to describe which and when food textures are offered to children between 4 and 36 months in France and to identify the associated factors. An online cross-sectional survey was designed, including questions about 188 food texture combinations representing three texture levels: purées (T1), soft small pieces (T2) and hard/large pieces and double textures (T3). Mothers indicated which combinations they already offered to their child. A food texture exposure score (TextExp) was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…The results from the present study support previously published work in the area. In the present study, as age increased, the textures of lumpy, mushy, and gooey/soggy/wet were all less likely to be reported as “easy.” These textures are more associated with pureed and baby foods, which as the child ages, generally decrease in consumption (Demonteil et al, ). Thus, the absence of these terms in the responses of the families of older children may have been due to the parent simply not considering these textures and including them in the open‐ended response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from the present study support previously published work in the area. In the present study, as age increased, the textures of lumpy, mushy, and gooey/soggy/wet were all less likely to be reported as “easy.” These textures are more associated with pureed and baby foods, which as the child ages, generally decrease in consumption (Demonteil et al, ). Thus, the absence of these terms in the responses of the families of older children may have been due to the parent simply not considering these textures and including them in the open‐ended response.…”
Section: Discussionmentioning
confidence: 99%
“…As the children got older, they became more accepting of the chopped texture (Blossfeld et al, 2007). In typically developing children, as the age of the child increases, a greater number of textures are introduced to the child (Demonteil et al, 2018). This recent study reported that over the first year, children were mainly exposed to purees, and between 6 and 22 months, soft and small pieces were introduced into the diet (Demonteil et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maturation of the masticatory function and related anatomical and physiological development of the orofacial sphere may be influenced by feeding practices and especially through consumption of diverse food textures throughout infancy and early childhood. Research papers report special interests in the optimal time frame to progressively introduce lumpy food and then solid food during the first 36 months of life, while national recommendations just advocate that texture should evolve according to the child's chewing skills (Demonteil et al, ). However, the time actually required to move from the suckling‐swallowing function in newborn, mostly based on reflex processes, to a fully developed chewing‐swallowing function requiring advanced coordination skills, is poorly documented, as well as the influencing factors of this process (Blossfeld, Collins, Kiely, & Delahunty, ; Coulthard, Harris, & Emmett, ; Fewtrell et al, ; Gisel, ; Stolovitz & Gisel, ; World Health Organization, ).…”
Section: Introductionmentioning
confidence: 99%